2009
DOI: 10.1007/s00011-008-8210-7
|View full text |Cite
|
Sign up to set email alerts
|

Highlights of a new type of intercellular communication: microvesicle-based information transfer

Abstract: Microvesicles (MVs) are membrane-covered cell fragments released by most cell types during apoptosis or activation. They are increasingly considered to play a pivotal role in information transfer between cells. Their presence and role have been proven in several physiological and pathological processes, such as immune modulation in inflammation and pregnancy, or blood coagulation and cancer. MVs represent a newly recognized system of intercellular communications. They not only may serve as prognostic markers i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
135
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(138 citation statements)
references
References 93 publications
2
135
0
1
Order By: Relevance
“…One-way ANOVA, followed by Bonferroni's post hoc test (c) or Student's t test (d) or repeated measures ANOVA, followed by Student's t test (e, f) was applied. n = 3 independent cultures for c and d, and n = 6 rats for e and f activation [42,43]. Our results indicated that, following SNL, P2X7 receptors and p38 were upregulated in a time-dependent manner (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…One-way ANOVA, followed by Bonferroni's post hoc test (c) or Student's t test (d) or repeated measures ANOVA, followed by Student's t test (e, f) was applied. n = 3 independent cultures for c and d, and n = 6 rats for e and f activation [42,43]. Our results indicated that, following SNL, P2X7 receptors and p38 were upregulated in a time-dependent manner (Fig.…”
Section: Discussionsupporting
confidence: 51%
“…1 The MV outer membrane provides one of the few protected and controlled internal microenvironments that exist outside cellular environments, in which complex interactions between, eg, hundreds of proteins, minerals, and proinflammatory molecules can occur, protected from, but still able to interact with, the extracellular environment. Outer membrane composition can not only be derived directly from the outer membrane of the host cell but can also contain intracellular membrane components.…”
Section: Introduction To the MV Environmentmentioning
confidence: 99%
“…1,2 MVs were identified to originate from a large number of cell types in vivo and in vitro: epithelial, fibroblast, hematopoetic, immune, placental, tumor and stem cells. 3,4 For long time, MVs were considered to be inert cellular debris and the vesicles frequently observed by electron microscopy in the interstitial space of tissues or in blood were considered the consequence of cell damage or the result of dynamic plasma membrane turnover. 5 Recent studies assigned specific functions to vesicles/exosomes released in the microenvironment by various cell types and in biological fluids, such as blood, urine, exudates.…”
Section: Introductionmentioning
confidence: 99%